SOFT DIPLOMACY TIONGKOK TERHADAP MESIR DALAM BIDANG KERJASAMA EKONOMI PERIODE 2016-2022 - Azmi, Agus Nilmada; Azaroh, Yuni Tamara; Lazuardi, Afried (An Nawawi, 2024)
This article discusses China's Soft Diplomacy efforts towards Egypt in the field of economic cooperation for the 2016-2022 period. China's relations with Egypt and the Middle East region previously experienced a decline after the Cold War, also the Arab Spring phenomenon which then destabilized China due to the impact of the economic and political crisis. China is improving relations with Egypt through a soft power approach to economic cooperation. Qualitative methods were used in this research through literature studies to find out how China's Soft Diplomacy approach towards Egypt in the field of economic cooperation and the interests of the two countries look at China's Belt and Road Initiative (BRI) and Egypt's Vision 2030. Based on the research conducted, it was found that China applies soft diplomacy in the field of economic cooperation in the form of establishing a strategic partnership between China and Egypt, where China emphasizes the use of institutional resources and values by offering the Belt and Road Initiative synergies. Besides that, China also has an interest in improving its positive image and expanding its influence in the Middle East Region.